2012
DOI: 10.1111/j.1467-985x.2011.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

The Synoptic Problem: On Matthew’s and Luke’s use of Mark

Abstract: Summary. In New Testament studies, the synoptic problem is concerned with the relationships between the gospels of Matthew, Mark and Luke. Assuming Markan priority, we investigate the relationship between the words in Mark that are retained unchanged by Matthew and those that are retained unchanged by Luke. This is done by mapping the sequence of words in Mark into binary time series that represent the retention or nonretention of the individual words, and then carrying out a variety of logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Their variable‐length Markov chains (VLMCs) and the associated model selection tools are based, in part, on Rissanen's tree sources and his context algorithm. The VLMC approach has been successful in applications (Busch et al, 2009; Mächler & Bühlmann, 2004) that include DNA modelling (Ben‐Gal et al, 2005; Browning, 2006) and linguistics (Abakuks, 2012; Galves et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Their variable‐length Markov chains (VLMCs) and the associated model selection tools are based, in part, on Rissanen's tree sources and his context algorithm. The VLMC approach has been successful in applications (Busch et al, 2009; Mächler & Bühlmann, 2004) that include DNA modelling (Ben‐Gal et al, 2005; Browning, 2006) and linguistics (Abakuks, 2012; Galves et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Their variable-length Markov chains (VLMCs) and the associated model selection tools are based, in part, on Rissanen's tree sources and his context algorithm. The VLMC approach has been successful in applications (Mächler and Bühlmann, 2004;Busch et al, 2009) that include DNA modelling (Ben-Gal et al, 2005;Browning, 2006) and linguistics (Galves et al, 2012;Abakuks, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A classic example of authorship attribution comes from Mosteller and Wallace (1963) who used grammatical features such as function word frequencies and word length distributions to determine whether 12 disputed essays in The Federalist Papers were written by James Madison or Alexander Hamilton. Other typical examples include Thisted and Efron (1987), where an alleged newly discovered Shakespeare poem was tested for authenticity, and Abakuks (2012) who used statistical techniques to investigate the relationship between the various authors of the Synoptic Gospels. Reviews of the related stylometry literature can be found in Juola (2006), Holmes (1985) and Peng and Hengartner (2002).…”
Section: Introductionmentioning
confidence: 99%